2020
DOI: 10.1021/jacs.9b12001
|View full text |Cite
|
Sign up to set email alerts
|

Helical Peptides Design for Molecular Dipoles Functionalization of Wide Band Gap Oxides

Abstract: The use of helical hexapeptides to establish a surface dipole layer on a TiO2 substrate, with the goal of influencing the energy levels of a coadsorbed chromophore, is explored. Two helical hexapeptides, synthesized from 2-amino isobutyric acid (Aib) residues, were protected at the N-terminus with a carboxybenzyl group (Z) and at the C-terminus carried either a carboxylic acid or an isophthalic acid (Ipa) anchor group to form Z-(Aib)6-COOH or Z-(Aib)6-Ipa, respectively. Using a combination of vibrational and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The spectra displayed a double-negative Cotton effect around 204 and 214 nm along with a positive peak at 196 nm, which is the characteristic pattern of the helical conformation built by short peptides. Compared with the spectrum of typical α-helix in proteins, the shorter length of the helix results in a slight blue-shift of the characteristic peaks by 3–7 nm and a lower intensity of the signals. , This result was also supported by attenuated total reflectance-infrared Fourier transform infrared (ATR-FTIR) and Raman spectra (Figures S7 and S8). The secondary structure assignment based on amide I and amide III bands showed that helical structures dominated the backbones of both heptapeptides.…”
Section: Resultsmentioning
confidence: 99%
“…The spectra displayed a double-negative Cotton effect around 204 and 214 nm along with a positive peak at 196 nm, which is the characteristic pattern of the helical conformation built by short peptides. Compared with the spectrum of typical α-helix in proteins, the shorter length of the helix results in a slight blue-shift of the characteristic peaks by 3–7 nm and a lower intensity of the signals. , This result was also supported by attenuated total reflectance-infrared Fourier transform infrared (ATR-FTIR) and Raman spectra (Figures S7 and S8). The secondary structure assignment based on amide I and amide III bands showed that helical structures dominated the backbones of both heptapeptides.…”
Section: Resultsmentioning
confidence: 99%